Self-templating construction of mesopores on three-dimensionally ordered macroporous La0.5Sr0.5MnO3 perovskite with enhanced performance for soot combustion. Issue 8 (19th March 2019) - Zhao, Peng; Fang, Fan; Feng, Nengjie; Chen, Chong; Liu, Geng; Chen, Li; Zhu, Zhongjian; Meng, Jie; Wan, Hui; Guan, Guofeng
Abstract : A three-dimensionally ordered macroporous (3DOM) La0.5 Sr0.5 MnO3 perovskite was prepared by a colloidal crystal templating method, with extra mesopores created by selective dissolution method performed successively. Abstract : A three-dimensionally ordered macroporous (3DOM) La0.5 Sr0.5 MnO3 perovskite was prepared by a colloidal crystal templating method, with extra mesopores created by selective dissolution method performed successively. Acid-nonresistant Sr cations acting as a self-template were dissolved by dilute nitric acid, making overstoichiometric Mn spill on to the surface of the perovskites, as confirmed according to the XRD, FTIR, XPS, and XRF results. Meanwhile, judging from TEM and N2 adsorption–desorption, mesopores could be produced after erosion, along with enlarged specific surface areas. On the one hand, the intact 3DOM structure could not only reduce the mass-transfer resistance, but also provided enough room for soot to enter. On the other hand, the mesopores and the higher surface areas may help accumulate active oxygen species and promote the oxidation of NO, which can accelerate soot combustion. However, excessive treatment may destroy the intact 3DOM structure, as indicated from the FESEM picture. Among all the as-prepared catalysts, LSM-3 showed superior reducibility and activity for soot combustion, as tested by XPS, H2 -TPR, O2 -TPD, soot-TPO, and NO-TPO techniques. The T 50 of LSM-3 was 435 °C/385 °C without/with NO, and the activation energy was 66 kJ mol −1 .